Market Access Professionals in the Pharmaceutical Industry in the United Kingdom: Essential Roles, Knowledge, Skills, and Attributes - Fatoye, Clara T.; Yeowell, Gillian; Miller, Eula; Odeyemi, Isaac; Mbada, Chidozie (Journal of Medical Science, 2025)
Introduction. Clearly defined roles and educational standards are crucial for enhancing professional status and facilitating Market Access (MA) in the pharmaceutical industry (pharma). However, literature on this topic remains limited. This study explored MA professionals’ roles within pharma in the United Kingdom (UK), including the knowledge, skills, competence, and other attributes required. Materials and methods. A document analysis of UK MA job advertisements from pharmaceutical companies, National Health Service websites, and Google search engine was undertaken between February and August 2019, and updated between 1st and 31st August 2023. Thematic content analysis was used to analyse the data. Results. Eighty advertisements met the inclusion criteria, classified by seniority: entry-level (44%), senior level (15%), pricing and reimbursement (11%), and head/director positions (30%). Entry-level roles displayed the most variability in titles. A degree in a relevant field was required for 86% of these positions, dropping to 38% for senior MA roles. While skills and activities varied, a strong understanding of healthcare systems and excellent communication skills were essential across all positions. The core attributes of MA professionals in pharma were defined by three MA components: ’right roles’ (job responsibilities), ’right people’ (reputation and skills), and ’right reward’ (wages and remuneration). Conclusions. This study is the first document analysis of MA job roles in pharma, focusing on their conceptualisation and definition. MA is an emerging profession characterised by diverse roles, varying entry requirements, and the need for collaboration across healthcare systems. The findings indicate that MA in pharma is still in the early stages of professionalisation and needs further development. To advance this evolution, developing competency frameworks, standardising job roles, and guiding curriculum design are recommended.